Analysis of Law No.8 of 1999 Concerning Consumer Protection Against Imported Products that Do Not Use Indonesian Language - Sahril Amin Lubis; Ramadani (Journal of Law, Politic and Humanities, 2024)
This research is motivated by prohibited acts for business actors contained in Article 8 paragraph 1 letter J of Law No. 8 of 1999 concerning consumer protection. The provisions for the inclusion of labels for imported products labeled in Indonesian are contained in Article 20 Paragraph (1) of PP No. 29 of 2021 concerning the Implementation of the Trade Sector, especially in CHAPTER III concerning the use or completeness of Indonesian-language labels which states that every business actor is obliged to use or complete Indonesian-language labels on goods traded domestically. Therefore, researchers are interested in researching this problem. The purpose of this research is to find out how the Imported Goods Products on the Use of Indonesian Language and to find out how the Law No. 8 Year 1999 on Consumer Protection Against Imported Goods Indonesian Language. Then the method used is a mix method, namely normative juridical review and empirical juridical review and the approach used is a statue approach and case approach and the source of legal material used is Law No. 8 of 1999 concerning consumer protection, books, articles, and journals. From the results of the analysis that the author conducted, it can be concluded that the determination of goods that are required to use Indonesian on a product has been clearly regulated in the Regulation of the Minister of Trade of the Republic of Indonesia Number 25 of 2021 concerning the Obligation to Include Labels in Indonesian, such as household goods, telecommunications, informatics, (for example fans, vaccum cleaners) building materials, motor vehicle goods (spare parts and others), textile goods and textile products and a list of other types of goods. Therefore, it is expected that business actors can include information on the label of a product using Indonesian language so that the information in the product is more easily understood by consumers.